Visualization of the Cervicothoracic Junction With EOS Imaging Is Superior to Conventional Lateral Cervical Radiographs. Issue 6 (July 2021) - Hirsch, Brandon P.; Vaynrub, Max; Siow, Matthew; Zou, Anthony; Anil, Utkarsh; Montes, Dennis Vasquez; Protopsaltis, Themistocles S.
Study Design: Single-center retrospective review. Objectives: The cervicothoracic junction (CTJ) is typically difficult to visualize using traditional radiographs. Whole-body stereoradiography (EOS) allows for imaging of the entire axial skeleton in a weightbearing position without parallax error and with lower radiation doses. In this study we sought to compare the visibility of the vertebra of the CTJ on lateral EOS images to that of conventional cervical lateral radiographs. Methods: Two fellowship-trained spine surgeons evaluated the images of 50 patients who had both lateral cervical radiographs and EOS images acquired within a 12-month period. The number of visible cortices of the vertebral bodies of C6-T2 were scored 0-4. Patient body mass index and the presence of spondylolisthesis >2 mm at each level was recorded. The incidence of insufficient visibility to detect spondylolisthesis at each level was also calculated for both modalities. Results: On average, there were more visible cortices with EOS versus XR at T1 and T2, whereas visible cortices were equal at C6 and C7. Patient body mass index was inversely correlated with cortical visibility on XR at T2 and on EOS at T1 and T2. There was a significant difference in the incidence of insufficient visibility to detect spondylolisthesis on EOS versus XR at C7-T1 and T1-2, but not at C6-7. Conclusions: EOS imaging is superior at imaging the vertebra of the CTJ. EOS imaging deserves further consideration as a diagnostic tool in the evaluation of patients with cervical deformity given its ability to produce high-quality images of the CTJ with less radiation exposure.